THE INFLUENCE OF SERVICE QUALITY AND DIGITAL MARKETING ON PURCHASE DECISION THROUGH BRAND AWARENESS AS AN INTERVENING VARIABLE AT SURYA MART UM SURABAYA - Moh Romli; Wiwik Handayani; Sugeng Purwanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the effect of service quality and digital marketing on purchase decision with brand awareness as a mediating variable in Surya Mart UM Surabaya. Using a quantitative approach and data from 95 respondents, the study employed the PLS-SEM method to analyze the relationships among variables. The results reveal that both service quality and digital marketing significantly affect brand awareness and purchase decision. Moreover, brand awareness was proven to mediate the relationship between the two independent variables and purchase decision. The findings highlight that tangible aspects such as cleanliness and neat product arrangement are highly valued by consumers, while appealing digital content enhances brand recognition and consumer trust. The implication is that optimizing customer service and marketing strategies not only boosts consumer engagement but also strengthens brand perception and loyalty. These results provide valuable insights for developing more effective marketing strategies in community-based retail businesses.